Functional Analyses of a Novel Splice Variant in the CHD7 Gene, Found by Next Generation Sequencing, Confirm Its Pathogenicity in a Spanish Patient and Diagnose Him with CHARGE Syndrome - Villate, Olatz; Ibarluzea, Nekane; Fraile-Bethencourt, Eugenia; Valenzuela, Alberto; Velasco, Eladio A.; Grozeva, Detelina; Raymond, F. L.; Botella, María P.; Tejada, María-Isabel (Frontiers in Genetics, 2018)
Mutations in CHD7 have been shown to be a major cause of CHARGE syndrome, which presents many symptoms and features common to other syndromes making its diagnosis difficult. Next Generation Sequencing of a panel of intellectual disability related genes was performed in an adult patient without molecular diagnosis. A splice donor variant in CHD7 (c.5665+1G>T) was identified. To study its potential pathogenicity, exons and flanking intronic sequences were amplified from patient DNA and cloned into the pSAD® splicing vector. HeLa cells were transfected with this construct and a wild-type minigene and functional analysis were performed. The construct with the c.5665+1G>T variant produced an aberrant transcript with an insert of 63 nucleotides of intron 28 creating a premature termination codon (TAG) 25 nucleotides downstream. This would lead to the insertion of 8 new amino acids and therefore a truncated 1896 amino acid protein. As a result of this, the patient was diagnosed with CHARGE syndrome. Functional analyses underline their usefulness for studying the pathogenicity of variants found by Next Generation Sequencing and therefore its application to accurately diagnose patients.